Evaluation of the saccharification and fermentation process of two different seaweeds for an ecofriendly bioethanol production. (April 2018) - Saravanan, Karunakaran; Duraisamy, Senbagam; Ramasamy, Gurusamy; Kumarasamy, Anbarasu; Balakrishnan, Senthilkumar
Abstract: The study is aimed to produce bioethanol and more specifically to provide a process for producing ethanol by the fermentation of macroalgal biomass. The seaweeds were evaluated for their hydrolysis process (acid and enzyme treatment). The hydrolysates obtained from acid and enzyme saccharification process were analysed for ethanol production to show the efficiency of hydrolysis processes. The content of reducing sugar after acid hydrolysis was found to be 60.6 ± 1.7 and 71 ± 1.6 mg/g biomass for Sargassum sp. and Gracilaria sp. respectively. Likewise, the biomass obtained from two stage hydrolysis, showed 110 ± 1.6 and 140.6 ± 1.7 mg/g biomass reducing sugar for the above mentioned two seaweeds. The yeast used for fermentation of ethanol was isolated from grape juice and identified by sequencing of large subunit (LSU) ribosomal DNA D1/D2 region of the yeast isolate. Maximum ethanol production (19.9 ± 0.3 and 28.7 ± 0.4 gL −1 for Sargassum sp. and Gracilaria sp. respectively) was significantly observed after two stage hydrolysis using Saccharomyces cerevisiae rather than Hanseniaspora opuntiae GK01 (18.37 ± 0.3 and 27.0 ± 0.6 gL −1 for Sargassum sp. and Gracilaria sp. respectively). This study is obviously proved that S. cerevisiae MTCC174 was found to be a better strain for ethanol production in both the seaweeds than the yeast strain isolated from grape juice H. opuntiae GK01. Highlights: Analysis of seaweeds biocomposition. Acid and enzyme hydrolysis of seaweeds. Bioethanol production with minimal cost and promotion of industrial scale up ecofriendly process using seaweeds as substrate.